The Relationship between Seaports and the Inter-Modal Hinterland in Light of Global Supply Chains - Notteboom, Theo (OECD/ITF Joint Transport Research Centre Discussion Papers, 2008)
The seaport-hinterland interaction plays an increasingly important role in shaping supply chain solutions of shippers and logistics service providers. Scarcity concerns combined with concerns over the reliability of transport solutions have led seaports and hinterland corridors to take up a more active role in supply chains. This contribution looks at port developments and logistics dynamics in Europe and proposes some steps towards a further integration between seaports and the hinterland. The key point put forward in this paper is that the competitive battle among ports will increasingly be fought ashore. Hinterland connections are thus a key area for competition and coordination among actors. The paper approaches port-hinterland dynamics from the perspective of the various market players involved, including port authorities, shipping lines, terminal operators, transport operators (rail, barge, road and short sea) and logistics service providers. The paper will address the impact of horizontal and vertical relations in supply chains on the structure of these chains and on the relationships between seaports and the intermodal hinterland. Who takes or should take the lead in the further integration of ports and inland ports and what actions have been taken so far by the market players in this respect, will be examined. The incentives for market players to vertically or horizontally integrate will be analyzed against the backdrop of the nature of the market in which the various players operate